Nature of positive emotions in the assessment of depression: A new view in psychometrics - Moscoso, Manolete S. (2014)
Current research in the field of emotions has demonstrated a strong causal correlation between stressful life events and clinical depression. The conceptual framework of this scientific study is taking into consideration the theoretical ideas developed by the laboratories of Alex Zautra, and Susan Folkman about the co-existence of positive and negative emotions during the experience of stress and depression. The principal purpose of this study is to report the convergent validity of the Multicultural State-Trait Depression Inventory, which supports the new direction in the psychometric assessment of clinical depression. Responses to the items of the state and trait scales were analyzed on a multicultural sample to determine the convergent validity and item analysis of the instrument. The results present empirical evidence that demonstrates a high degree of concurrent validity of the IMUDER subscalesand the reference instruments as shown by Pearson correlations.